Does the Source of Foreign Direct Investment Matter to Economic Growth in Malaysia?. Issue 2 (3rd April 2018) - Tang, Chor Foon; Tan, Eu Chye
Abstract: Foreign direct investment (FDI) is often viewed as a potential contributor to a country's economic growth and development. However, the extent of the contribution may depend upon the source of such investment inflows. This paper assesses the contribution of inward FDI to Malaysia's economic growth using investment data disaggregated by source over the period, 2008:Q1–2016:Q3. Due to the mixed orders of integration of the series involved, the autoregressive distributed lag (ARDL) framework is employed to conduct the assessment. The econometric results indicate that the source of the FDI does matter greatly when considering the extent of its spin-off for the local economy. Specifically, FDI flows from North America and Southeast Asia contribute more significantly to Malaysia's economic growth than FDI flows from Central and South America, Northeast Asia and Oceania.